Pengaruh Permainan Edukatif Make A Match dalam Layanan Bimbingan Kelompok terhadap Keterampilan Sosial Siswa - Hasyalma Fitriyana; Ali Rachman; M. Andri Setiawan (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
Social skills are important abilities that students need to support effective communication, cooperation, and interaction in the school environment. However, there are still students who have not been able to demonstrate social skills optimally. Therefore, this study was conducted to determine the effect of the Make A Match educational game in group guidance services on students' social skills. This study employed a quantitative method with a One Group Pretest-Posttest design, which is included in the Pre-Experimental Design category. The research subjects consisted of six seventh-grade students of SMP Negeri 25 Banjarmasin selected through purposive sampling. The research data were collected using a social skills questionnaire that had passed validity and reliability testing. The data were analyzed using descriptive statistics and the Wilcoxon Signed Rank Test. The results showed an improvement in students' social skills, indicated by an increase in the mean score from 105.33 before the treatment to 154.67 after the treatment. In addition, the hypothesis testing result obtained a significance value of 0.027 (< 0.05), indicating that the alternative hypothesis was accepted. Thus, the use of the Make A Match educational game in group guidance services was proven effective in improving students' social skills. his study was conducted on a limited sample of six students using a One Group Pretest-Posttest design without a control group. Therefore, the findings are limited to the research subjects and should be generalized with caution. Nevertheless, the results indicate that the Make A Match educational game can be used as an alternative technique in group guidance services to improve students' social skills.